Bilinçli Farkındalık Temelli Stres Azaltma Programının Yaşlılarda Algılanan Stres ve Geriatrik Depresyon Düzeyine Etkisi - Yıldız, Mükerrem Kabataş (My University, 2022)
Amaç: Bu araştırmanın amacı Bilinçli Farkındalık Temelli Stres Azaltma (MBSR) programının yaşlılarda algılanan stres ve geriatrik depresyon düzeyine etkisini belirlemektir. Materyal ve Metot: Randomize kontrollü deneysel türde olan bu araştırmanın verileri Mayıs- Kasım 2021 tarihleri arasında Samsun ilindeki bir huzurevinde kalan yaşlı bireylerden elde edilmiştir. Araştırmanın evrenini huzurevinde kalan 54 yaşlı birey, örneklem grubunu ise bu bireylerden dahil edilme kriterlerini karşılayan 48 yaşlı birey (24 deney, 24 kontrol grubu) oluşturmuştur. Araştırma kapsamında deney grubundaki yaşlı bireylere araştırmacı tarafından yaşlılara yönelik uyarlanan MBSR programı uygulanmıştır. Veriler Kişisel Bilgi Formu, Algılanan Stres Ölçeği ve Geriatrik Depresyon Ölçeği-Kısa Form kullanılarak toplanmıştır. Verilerin analizinde, Ki-kare Testi, Bağımsız örneklem t-testi ve Karışık ölçümler için iki faktörlü ANOVA testleri kullanılmıştır. Bulgular: Deney ve kontrol grubundaki yaşlı bireylerin algılanan stres toplam, yetersiz özyeterlik, stres/rahatsızlık algısı alt boyutları ve geriatrik depresyon puanları arasında öntest ölçümlerine göre anlamlı farklılık bulunmazken, sontest-1 ve sontest-2 ölçümleri açısından deney grubu yönünde anlamlı farklılık olduğu saptanmıştır. Deney grubundaki yaşlı bireylerin algılanan stres toplam, yetersiz özyeterlik ve stres/rahatsızlık algısı alt boyutları ve geriatrik depresyon öntest puanları ile sontest-1 ve sontest-2 ölçümleri arasında anlamlı farklılık olduğu belirlenmiştir. MBSR uygulamasının yaşlı bireylerin algılanan stres toplam puanlarında %54,7 ve alt boyutlardan yetersiz özyeterlik algısı puanlarında %49,9, stres/rahatsızlık algısı puanlarında %49,8; geriatrik depresyon puanlarında %14,1 düzeyinde anlamlı ve geniş bir etki oluşturarak azaltma sağladığı saptanmıştır. Sonuç: MBSR programının yaşlıların algıladıkları stres ve geriatrik depresyon düzeylerini azaltmada etkili bir yöntem olduğu; uygulama bittikten bir ay sonrasında da bu etkinin korunduğu sonucuna ulaşılmıştır. Yaşlı bireylerin ruh sağlığının korunması ve geliştirilmesine yönelik hemşirelik uygulamalarında MBSR programının yöntem olarak kullanılması önerilmektedir. Anahtar Sözcükler: Algılanan stres, bilinçli farkındalık, geriatrik depresyon, hemşirelik, yaşlı ruh sağlığı

Aim: The aim of this study is to find out the effects of Mindfulness Based Stress Reduction (MBSR) program on perceived stress and geriatric depression level in elderly individuals. Material and Method: The data of this randomized controlled experimental study was collected from elderly individuals staying in a nursing home in Samsun between May and December 2021. Population of the study consisted of 54 elderly individuals staying in the nursing home, while the sample group consisted of 48 individuals (24 experimental, 24 control group) who met the inclusion criteria. Within the scope of the study, MBSR program adapted to elderly individuals was applied to the elderly individuals in the experimental group by the researcher. The data were collected with Personal Information Form, Perceived stress scale and Geriatric-Depression Scale-Short Form. In data analysis, Chi-square test, Independent Samples and two-way ANOVA tests for mixed measurements were used in data analysis. Results: While no significant difference was found between perceived stress total, insufficient self-efficacy, stress/discomfort perception sub-scales and geriatric depression scores of elderly individuals in the experimental and control groups in terms of pre-test measurements, significant difference was found in terms of posttest-1 and posttest-2 measurements in favour of the experimental group. A significant difference was found between pretest scores with posttest-1 and posttest-2 measurements in terms of perceived stress total, insufficient self-efficacy, stress/discomfort perception subscales and geriatric depression scores of the elderly individuals in the experimental group. It was found that MBSR practice caused significant and large effects of 54.7% in perceived stress total scores, 49.9% in insufficient self-efficacy perception scores, 49.8% in stress/discomfort perception scores and 14.1% in geriatric depression scores of elderly individuals and decreased these scores. Conclusion: It was concluded that MBSR program is an effective method in decreasing perceived stress and geriatric depression levels of elderly individuals and this effect was maintained a month after the program was completed. It is recommended for MBSR program to be used as a method in nursing practices aimed at protecting and improving the mental health of elderly individuals. Keywords: Perceived stress, mindfulness, geriatric depression, nursing, elderly mental health
The Effect of Mindfulness Based Stress Reduction Program on Perceived Stress and Geriatric Depression Level in the Elderly
Keywords: Hemşirelik; Bilinçli Farkındalık; Depresyon; Farkındalık; Geriatri; Nursing; Mindfulness; Ruh Sağlığı; Depression; Awareness; Stres; Geriatrics; Mental Health; Stres Yönetimi; Stress; Stress Management; Yaşlılar; Aged